2004
DOI: 10.1002/mus.20121
|View full text |Cite
|
Sign up to set email alerts
|

Motor conduction studies for prognostic assessment of obstetrical plexopathy

Abstract: Early prognostic assessment of obstetrical brachial plexopathies (OBP) would facilitate rational selection of infants for brachial plexus surgery. We performed bilateral motor nerve conduction studies (MNCS) of axillary, musculocutaneous, radial, median, and ulnar nerves in 33 babies (age 10-60 days) with OBP in order to compare the amplitude of compound muscle action potentials (CMAPs). All babies were followed up until 6 months of age and the outcome was classified according to muscle strength and arm functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…Our group has been doing this based on motor conduction studies, and the results have been encouraging. 32 We think that needle EMG performed between 3 to 12 months of age is not helpful to the surgeon regarding the indication of surgery. As a matter of fact, we are not using it anymore.…”
Section: Discussionmentioning
confidence: 98%
“…Our group has been doing this based on motor conduction studies, and the results have been encouraging. 32 We think that needle EMG performed between 3 to 12 months of age is not helpful to the surgeon regarding the indication of surgery. As a matter of fact, we are not using it anymore.…”
Section: Discussionmentioning
confidence: 98%
“…Noaman et al (2004) applied Oberlin's nerve transfer in Erb's birth palsy and mentioned that clinicians must be aware of the numerous variations of the course, branching patterns, and communications of the MCN. Heise et al (2004) reported that early prognostic assessment of obstetrical brachial plexopathies would facilitate rational selection of infants for brachial plexus surgery; so, they performed bilateral motor nerve conduction studies of the MCN to compare the amplitude of compound muscle action potentials. Murphy and Chan (2000) emphasized that to provide upper limb regional anesthesia effectively and efficiently, the physician must be clear on the sensory and motor innervations to the site of surgery for improving success and limiting complications.…”
Section: Discussionmentioning
confidence: 99%
“…The most likely cause for this difference is that the neuroma resection (in nerve grafting) or nerve transection (in nerve transfer) interrupts pathways that include nerve fibres misdiagnosed as nonviable. Possible mechanisms for misdiagnosis are: a) relying solely on the physical examination of biceps flexion; 22,23 b) failing to appreciate the frequent presence of cocontraction between biceps and triceps in which the overly strong and early triceps recovery will mask effective biceps recovery; 24,25 c) assuming that intra-operative nerve conduction studies at the site of the neuroma results in a valid evaluation of the amount of viable nerve within the neuroma. It may be that the common presence of dense epineural scarring insulates recovering and uninjured axons from the current produced by the stimulating electrode, thereby resulting in a false-negative impression of viable nerve status; d) operating on these children between three and six months of age is too early to allow effective assessment of the recovery potential of the injured brachial plexus nerves.…”
Section: Discussionmentioning
confidence: 99%